Dynamic changes in CGRP, PACAP, and PACAP receptors in the trigeminovascular system of a novel repetitive electrical stimulation rat model: Relevant to migraine. (January 2019) - Zhang, Qing; Han, Xun; Wu, Hangfei; Zhang, Mingjie; Hu, Guanqun; Dong, Zhao; Yu, Shengyuan
Migraine is the seventh most disabling disorder globally, with prevalence of 11.7% worldwide. One of the prevailing mechanisms is the activation of the trigeminovascular system, and calcitonin gene-related peptide (CGRP) is an important therapeutic target for migraine in this system. Recent studies suggested an emerging role of pituitary adenylate cyclase-activating peptide (PACAP) in migraine. However, the relation between CGRP and PACAP and the role of PACAP in migraine remain undefined. In this study, we established a novel repetitive (one, three, and seven days) electrical stimulation model by stimulating dura mater in conscious rats. Then, we determined expression patterns in the trigeminal ganglion and the trigeminal nucleus caudalis of the trigeminovascular system. Electrical stimulation decreased facial mechanical thresholds, and the order of sensitivity was as follows: vibrissal pad >inner canthus >outer canthus (P < 0.001). The electrical stimulation group exhibited head-turning and head-flicks (P < 0.05) nociceptive behaviors. Importantly, electrical stimulation increased the expressions of CGRP, PACAP, and the PACAP-preferring type 1 (PAC1) receptor in both trigeminal ganglion and trigeminal nucleus caudalis (P < 0.05). The expressions of two vasoactive intestinal peptide (VIP)-shared type 2 (VPAC1 and VPAC2) receptors were increased in the trigeminal ganglion, whereas in the trigeminal nucleus caudalis, their increases were peaked on Day 3 and then decreased by Day 7. PACAP was colocalized with NEUronal Nuclei (NeuN), PAC1, and CGRP in both trigeminal ganglion and the trigeminal nucleus caudalis. Our results demonstrate that the repetitive electrical stimulation model can simulate the allodynia during the migraine chronification, and PACAP plays a role in the pathogenesis of migraine potentially via PAC1 receptor.